Welcome to beach town : a novel - Wiggs, Susan (William Morrow, 2023)
"Beloved New York Times bestselling author Susan Wiggs returns with a compulsively readable tale of an idyllic California beach town forced to reckon with scandal when a high school valedictorian's speech reveals secrets that shake the town to its core"--